PENGARUH AUDITOR TENURE, UKURAN KANTOR AKUNTAN PUBLIK, DAN UKURAN PERUSAHAAN KLIEN TERHADAP KUALITAS AUDIT (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2010-2012) - Putri, Tifani Malinda; Cahyonowati, Nur (Diponegoro Journal of Accounting, 2014)
The purpose of this paper is to examine the influence of auditor tenure, audit firm size, and client size on audit quality as measured by the level of discretionary accrual on the manufacturing companies listed on the Indonesia Stock Exchange in 2010 until 2012. Auditor tenure, audit firm size, and client size as the independent variables and the quality audit that proxied by discretionary accrual as the dependent variable. This study used data of 69 manufacturing companies listed in Indonesia Stock Exchange from 2010 until 2012. Data from this study were obtained from annual report and auditing report of manufacturing firms which drawn from the Indonesia Stock Exchange and Indonesian Capital Market Directory. Determination of the sample using purposive sampling method. Type of data are secondary data in the form of financial statement as the media manufacturing companies. Data analysis tool is multiple linear regression model. The results of this study indicate that auditor tenure and client size have significant impact on audit quality as measured by the level of discretionary accrual. Meanwhile audit firm size that proxied by BIG 4 auditor and non BIG 4 auditor has no significant impact on audit quality as measured by the level of discretionary accrual.